Perancangan Video Iklan Produk Jamu Tradisional Di Desa Nguter Untuk Remaja - Yastaqim, Naufal Galang; Khoirul Anwar, Ahmad; Yulianto, Arif (JURNAL KEMADHA, 2026)
Traditional medicine is a health product made from natural ingredients processed according to local wisdom. Traditional medicine is made from ingredients chosen by teenagers as a supplement to maintain their health. Kautsar 2024 revealed that 88 respondents (78.6%) had used the supplement effectively, while 24 respondents (21.4%) experienced adverse side effects, categorizing it as a negative outcome. Based on these issues, the design of a traditional medicine advertisement video for teenagers is expected to provide information about the benefits of consuming traditional medicine for maintaining health. The objective of this design is to provide teenagers with information about the benefits of traditional medicine for maintaining health. This design used a video advertisement to convey information about traditional medicine for maintaining health. This design method used design thinking, which consists of five stages: empathize, define, ideate, prototype, and test. The result of this design is a traditional medicine advertisement video entitled " Dari Alam Untuk Generasi Masa Kini." Through this advertisement video, teenagers can better understand information about traditional medicine and the benefits of consuming traditional medicine for health.